Forthcoming Meetings Of Societies (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1918)
Organization Place Date 1918 National Society of Naval Architects New York, N. Y. Nov. 14-15 American Society of Mechanical Engineers New York, N. Y. Dec. 3-6 Geological Society of America Boston, Mass. Dec. 28-31 American Association for the Advancement of Science Boston, Mass. Dec. 27¬ Jan. 2. 1919 American Society of Civil Engineers New York, N. Y. Jan. 15-16 American Wood Preservers Association St. Louis, Mo. Jan. 28-30 American Society of Heating and Ventilating Engi¬ neers New York, N. Y. Jan. 28-30